Introduction to Critical Thinking in Educational Model for Visual Communication Design Methods: Study Case Design Methods Class for Visual Communication Design Program at Binus University, Indonesia - Adele, Patricia Penina; Wulandari, Sari (Bina Nusantara University, 2024)
Based on the Programme for International Students Assessment (PISA), where problem-solving skills and critical thinking were measured the Indonesian students ranked below standard. In a smaller scope, there were other phenomenon in the learning process of a Design Methods class, in the Visual Communication Design programme at Binus University where students struggled to perform design analysis specifically on the part where the process of classifying which data belong to each of the three analytical aspects of the Triadic, despite definitions had been given in the prior session. In The Ethics, Aristotle thought about classifying as one of the thinking processes that would help in the process of analyzing. According to the Reboot Foundation, an institution dedicated to critical thinking research in the United States of America, critical thinking is needed in the decision-making process. The study was conducted to find the influence of the addition critical thinking method in C-F-C Triadic, one of the design thinking methods, in its learning process. The method in this investigation is qualitative primary data collection based on the observation of two different classes, class A and class B. In class A, the learning process was given following the existing learning process, while in class B, an additional short critical thinking demo was given in the first session of the class. The result was elevation in the analysis performance of the students in class B.